Lame science? Blind religion? - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 2019)
In Consecrating Science, Lisa Sideris argues that an anthropocentric and science-based cosmology encourages human arrogance and diminishes a sense of wonder in human experience immersed in the natural world, found in diverse cultural and religious traditions. I agree with her that science elevated to a commanding world view, scientism, is a common and contemporary mistake, to be deplored, a lame science. But I further argue that science has introduced us to the marvels of deep nature, and vastly increased our human appreciation of nature as a wonderland at levels great and small. Sideris is right to fear consecrating science. She—and the humanists, sages, and saviors—need also to fear blindness to what science has to teach us about cosmogenesis and wonderland Earth.
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: cosmogenesis; Sideris, Lisa; science; religion; wonder; wonderland Earth